Edukasi Perubahan Iklim (EPI) Pelajar Sekolah Menengah: Perubahan Pengetahuan dan Sikap - Mulyanti, Heri (Turast: Jurnal Penelitian dan Pengabdian, 2024)
Global warming is a problem that will be faced by all young generations. The younger generation is expected to be the vanguard of a resilient society in the face of climate change, which is a result of global warming. The service is aimed at senior high school students (middle school age) at MTs Muhammadiyah Banjarnyar, Baureno, Bojonegoro Regency in April 2023. The activities take the form of socialization, discussions, and comparisons between pre-tests and post-tests. Pre- and post-event tests encompass aspects of knowledge and attitude. The service is expected to provide an understanding for students regarding the phenomena, actions, and reactions to climate change. The knowledge aspect shows an increase, while the attitude aspect does not exhibit a significant positive change. An educational program is needed to guide students to witness the effects of climate change firsthand, thereby transforming it into tangible actions.